Astaxanthin ameliorates behavioral and biochemical alterations in in-vitro and in-vivo model of neuropathic pain. (1st May 2018) - Sharma, Kuhu; Sharma, Dilip; Sharma, Monika; Sharma, Nishant; Bidve, Pankaj; Prajapati, Namrata; Kalia, Kiran; Tiwari, Vinod
Highlights: Astaxanthin fits into the inhibitory binding pocket of NMDA receptor (NR2B) which is known to be involved in nociception. This suggests that astaxanthin may have antagonistic properties for NR2B receptors and can be used against neuropathic pain. Astaxanthin decreases oxido-nitrosative stress and GFAP expression in LPS treated C6 glial cells. Astaxanthin showed decrease in mechanical and thermal hypersensitivity in CCI-induced neuropathic rats. Abstract: Despite considerable advances in understanding mechanisms involved in chronic pain, effective treatment remains limited. Astaxanthin, a marine natural drug, having potent anti-oxidant and anti-inflammatory activities is known to possess neuroprotective effects. However, effects of astaxanthin against nerve injury induce chronic pain remains unknown. Overactivity of glutamatergic NMDARs results in excitotoxicity which may participate in astrocytic and microglial activation during pathology which further contribute to the development of neuropathic pain. In this study, we investigate the effects of astaxanthin on oxido-inflammatory and NMDA receptor down-regulation pathway by using in-silico, in-vitro and in-vivo models of neuropathic pain. In-silico molecular docking study ascertained the binding affinity of astaxanthin to NMDA receptors and showed antagonistic effects. Data from in-vitro studies suggest that astaxanthin significantly reduces the oxidative stress induced by the lipopolysaccharides in C6 glial cells. In male Sprague dawley rats, a significant attenuation of neuropathic pain behavior was observed in Hargreaves test and von Frey hair test after astaxanthin treatment. Findings from the current study suggest that astaxanthin can be used as potential alternative in the treatment of chronic neuropathic pain. However, more detailed investigations are required to further probe the in-depth mechanism of action of astaxanthin.